2011
DOI: 10.2166/wh.2010.063
|View full text |Cite
|
Sign up to set email alerts
|

Variability of E. coli density and sources in an urban watershed

Abstract: The objective of this study was to characterize the variability of Escherichia coli density and sources in an urban watershed, particularly to focus on the influences of weather and land use.E. coli as a microbial indicator was measured at fourteen sites in four wet weather events and four dry weather conditions in the upper Blackstone River watershed. The sources of E. coli were identified by ribotyping. The results showed that wet weather led to sharp increases of E. coli densities. Interestingly, an intense… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…A similar phenomenon has been observed in an urban watershed, where heavy storms led to an increase in E. coli concentration. 34 The results showed air temperature has a complicated relationship with E. coli presence and concentration, which might be explained as follows. First, air temperature does not have a linear relationship with groundwater temperature.…”
Section: Discussionmentioning
confidence: 99%
“…A similar phenomenon has been observed in an urban watershed, where heavy storms led to an increase in E. coli concentration. 34 The results showed air temperature has a complicated relationship with E. coli presence and concentration, which might be explained as follows. First, air temperature does not have a linear relationship with groundwater temperature.…”
Section: Discussionmentioning
confidence: 99%
“…High variability in measurements of indicator concentrations have been observed in this study region 32 and in temperate coastal waters 33 from short to long timescales. Wu and others 34 found that the density of E. coli in an urban watershed in Massachusetts displayed a high degree of spatial and temporal variability, and was highly influenced by both weather and surrounding land use. Wide variability has been observed between the ten U.S. EPA-approved tests to detect and quantify total coliforms and E. coli.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of precipitation and streamflow in the transport of protozoan and bacterial pathogens and fecal indicator bacteria in lotic systems has been frequently reported (Ferguson et al, 2003;Dorner et al, 2006;Wu et al, 2011;Duris et al, 2013), but only a handful of studies have related these environmental factors to virus transport and the findings have not been consistent. Rainfall or elevated river flow was associated with increased detection frequencies or increased virus concentrations at various sites in the area near Galveston, TX (Gerba et al, 1979), the Chicago area waterway system (Rijal et al, 2009), and the Atlamaha River, Georgia .…”
Section: Discussionmentioning
confidence: 99%